Experimental investigation on anti-falling protection systems for reinforced concrete-brick composite floors. (1st February 2023) - Franceschini, Lorenzo; Belletti, Beatrice; Ferretti, Daniele; Sirico, Alice; Ravasini, Simone; Pagliari, Federico; Vitali, Andrea; De Berardinis, Paolo
Highlights: Anti-falling protection systems for existing floors of reinforced concrete and bricks. Full-scale experimental tests up to failure on galvanised electro-welded steel wire meshes. Higher load and lower displacement at failure for the protection system including plaster. Abstract: Reinforced concrete and brick composite floors are typical features of Italian buildings. In these floors, falling debris caused by the detachment of non-structural parts - such as portions of brick, plaster, or concrete joist cover - is quite frequent. To prevent injuries to people and economic losses due to property damage, nowadays public authorities and companies invest considerable resources to install fall protection systems on existing floors. In this context, the present work is addressed to the experimental investigation of the performance and failure mechanism of anti-falling protection systems composed of galvanised electro-welded steel wire meshes attached to the intrados of the slab. Tests are performed under quasi-static concentrated loads up to failure. Two configurations of the protection system are analysed: with and without the presence of plaster. Experimental findings show that: (i) the electro-welded steel wire mesh can withstand considerable load up to failure (ii) the application of plaster layer modifies the failure mode and considerably increases the load-bearing capacity and the stiffness of the system. Based on the experimental investigation, the study: (i) experimentally confirms the effectiveness of this method as an anti-fall system, and (ii) provides information about the behaviour of the system that is essential for its modelling.